Characteristics of fluid dynamics in tubes and the outflow tract of an artificial heart, measured with pulsed US Doppler technique - M. POHL; M. O. WENDT; G. PARDEMANN; D. LERCHE (Archives of Acoustics)
Velocity profiles and turbulence intensities of steady flow in tubes were measured with a pulsed ultrasonic-Doppler instrument IMP 30. These results were compared with those of other flow measurement methods. In a similar way such measurements were performed to study pulsatile flow in the inflow- and the outflow-tract of an artificial heart, developed by the Hospital of Internal Medicine, Wilhelm-Pieck-University, Rostock. The principles of signal acquisition and first results are presented.